Turbinoplasty by laser - Rahman, Md Zillur; Hossain, ABM Tofazzal (Bangladesh Journal of Otorhinolaryngology, 2010)
This is a study of 61 cases of turbinoplasty done in 3 hospitals of Bangladesh from August 2007 to July 2009 (2 years). This study compares turbinoplasty by laser with that of non-laser techniques. 60.65% of patients were operated by laser and 39.34% of patients were operated by non-laser techniques. Majority of the patients were from 21- 40 years of age, (62.16% in laser group and 54.16% in non-laser group). Male & Female patients ratio was 3:1 in both groups. 100% of the patients were presented with nasal obstruction. 98.36% with nasal discharge, 95.08% with headache and 75.40% with frequent sneezing (p<0.01). Most patients were operated under local anesthesia in both groups (78.38% and 58.33% respectably). Follow up was satisfactory up to 3 months (Laser group 81.08 % and non-laser group 70.83 %). Most of the patient were all symptoms free (86.48 % in laser group and 79.16 % in nonlaser group). Only 8 patients (21.62%) present with crusting in laser group in respect to 22 patients (91.66%) in non-laser group with no incidence of severe post–operative nasal bleeding in laser group. 34 patients (91.89%) of Laser group and 13 patients (35.13%) of non-laser group were treated as day care surgery. Most of the cases (70.27%) were operated by diode laser. Recurrences of symptoms were negligible in laser group (2.70%). Key Words: Laser; Turbinoplasty. DOI: 10.3329/bjo.v16i1.5775 Bangladesh J Otorhinolaryngol 2010; 16(1): 9-14